PTBP1 contributes to spermatogenesis through regulation of proliferation in spermatogonia - Manami SENOO; Takashi TAKIJIRI; Nobuaki YOSHIDA; Manabu OZAWA; Masahito IKAWA (The Journal of Reproduction and Development, 2018)
Polypyrimidine tract-binding protein 1 (PTBP1) is a highly conserved RNA-binding protein that is a well-known regulator of alternative splicing. Testicular tissue is one of the richest tissues with respect to the number of alternative splicing mRNA isoforms, but the molecular role(s) of PTBP1 in the regulation of these isoforms during spermatogenesis is still unclear. Here, we developed a germ cell–specific Ptbp1 conditional knockout (cKO) mouse model by using the Cre-loxP system to investigate the role of PTBP1 in spermatogenesis. Testis weight in Ptbp1 cKO mice was comparable to that in age-matched controls until 3 weeks of age; at ≥ 2 months old, testis weight was significantly lighter in cKO mice than in age-matched controls. Sperm count in Ptbp1 cKO mice at 2 months old was comparable to that in controls, whereas sperm count significantly decreased at 6 months old. Seminiferous tubules that exhibited degeneration in spermatogenic function were more evident in the 2-month-old Ptbp1 cKO mice than in controls. In addition, the early neonatal proliferation of spermatogonia, during postnatal days 1–5, was significantly retarded in Ptbp1 cKO mice compared with that in controls. An in vitro spermatogonia culture model (germline stem cells) revealed that hydroxytamoxifen-induced deletion of PTBP1 from germline stem cells caused severe proliferation arrest accompanied by an increase of apoptotic cell death. These data suggest that PTBP1 contributes to spermatogenesis through regulation of spermatogonia proliferation.